Clinical profile, prognostication and treatment outcomes in non Hodgkins lymphoma - Dubey, A. P.; Singh, Rajeshwar; Pathak, Abhishek; Viswanath, S.; Rathore, Anvesh; Pathi, Nikhil (International Journal of Advances in Medicine, 2017)
Background: Non Hodgkins lymphoma is the most prevalent hematopoietic neoplasm, representing approximately 4% of all cancer diagnoses and ranking seventh in frequency among all cancers. Most of the data that we have is of west and data pertaining to Indian subcontinent is lacking. The aim of this study was to study clinical profile, prognostication, and assess treatment outcome in DLBCL patients in a tertiary care hospital. Methods: 100 patients of DLBCL reporting to a tertiary care hospital between 2013 to 2016 were chosen for the study. All patients were subjected to routine investigation and specialized investigation including bone marrow examination and Positron emission tomography. Patients were treated with standard treatment protocol and their response to treatment were assessed. Results: Study revealed male predominance with median age of onset was 45.6. Anorexia was the most common symptom. Lymphadenopathy was the most common sign. Bone marrow involvement and anemia commensurate each other. Only16% cases presented in IPI score 4 and 5. Complete remission achieved with treatment in stage l and ll disease were beyond 90% and steep decline in complete remission with treatment was noted in stage lll and lV ( 70%). 76% patients with DLBCL showed CR, 12.5% showed PR. Conclusions: The present study revealed male preponderance with relatively early age of onset compared to western population. B- cell lymphoma (DLBCL) constituted maximum number of NHL cases (89%). We have found a higher proportion of B cell subtype as compared to other Indian studies, at the same time it corroborated with the findings of western studies. Complete remission achieved with treatment in stage l and ll disease were beyond 90% and steep decline in complete remission with treatment was noted in stage lll and lV ( 70%).